Förändring och kontinuitet Reformer inom högre utbildning och forskning 1940-2020 - Gribbe, Johan (Universitetskanslersämbetets publikationer, 2022)
In the past eighty years, the Swedish university and higher education sector has undergone major changes. The conditions for conducting higher education and research have fundamentally changed. Universities and colleges have evolved from narrow elite institutions to educating large sections of the population and have increasingly attracted the interest of politics. They are located throughout the country and have gradually been assigned greater and greater resources and responsibilities. The majority of publicly funded research is currently conducted at the country's universities. At the same time, the sector's development has been characterized by considerable continuity. It is impossible to understand the structure of today's Swedish higher education landscape without taking into account the background and historical development of the universities and colleges. This report deals with developments in the period 1940-2020. The starting point is the state's reforms in higher education and research. It is both about broad, overarching reforms that affected large parts of the activities at universities and colleges in one context and about the continuous adaptation of regulations and systems. The purpose is to draw an overview of the development of the modern Swedish university. The report is primarily aimed at people working at universities and authorities, but also at politicians and people from the interested public who want to know more about the background to today's university and college system and why it looks the way it does. The report has been prepared by the University Chancellor's Office, as part of the mission to follow developments in Swedish higher education and research. The University Chancellor's Office also annually publishes up-to-date statistics on the Swedish university and a large number of reports on various themes.